Effect of components on the microstructures and properties of rare-earth zirconate ceramics prepared by ultrafast high-throughput sintering. Issue 11 (September 2021) - Zhao, Zhi-Tao; Guo, Rui-Fen; Mao, Hai-Rong; Shen, Ping
Graphical abstract: Abstract: Rare-earth zirconate ceramics are conventionally sintered at high temperatures for long durations to achieve a full density. Herein, we synthesized and densified five lanthanide-group rare-earth zirconates (Ln2 Zr2 O7, Ln = La, Nd, Sm, Eu, Gd) containing different numbers of Ln cations in a high-throughput mode using a novel ultrafast high-temperature sintering technique within a cycle of 5 min, and investigated the effects of components on the structure and properties of the resultant ceramics. Under the high-throughput mode, the same sintering conditions make the analysis and comparison of the results more reasonable. The average grain size decreased while hardness and Young's modulus increased with an increase in the number of the Ln components in the zirconate ceramics. The mechanisms were ascribed to the sluggish diffusion and lattice distortion effect caused by the increase in entropy.